Genetic Characteristics of Porcine Hemagglutinating Encephalomyelitis Coronavirus: Identification of Naturally Occurring Mutations Between 1970 and 2015 - Bahoussi, Amina Nawal; Guo, Yan-Yan; Shi, Rui-Zhu; Wang, Pei-Hua; Li, Ya-Qian; Wu, Chang-Xin; Xing, Li (Frontiers in Microbiology, 2022)
Porcine hemagglutinating encephalomyelitis virus (PHEV) is a Betacoronavirus characterized by neurological symptoms and a worldwide prevalence. Although PHEV is one of the earliest discovered porcine coronaviruses, it remains poorly studied. The full-length genome of the earliest PHEV strain collected in 1970 in the United States (PHEV/67 N/US/1970) was determined in October 2020. Using this virus as a prototype, we comparatively analyzed all available PHEV full-length sequences during 1970–2015. In phylogenetic trees based on PHEV full-length or spike glycoprotein open reading frame genomic sequences, PHEV/67 N/US/1970 was sorted into a clade different from that of viruses isolated in the United States in 2015. Intriguingly, United States and Belgium viruses isolated in 2015 and 2005, respectively, revealed multiple deletion mutation patterns compared to the strain PHEV/67 N/US/1970, leading to a truncated or a non-functional NS2A coding region. In addition, the genomic similarity analysis showed a hypervariability of the spike glycoprotein coding region, which can affect at least eight potential linear B cell epitopes located in the spike glycoprotein. This report indicates that PHEVs in the United States underwent a significant genetic drift, which might influence PHEV surveillance in other countries.